The effects of CCK-8S on spatial memory and long-term potentiation at CA1 during induction of stress in rats - Malihe Sadeghi; Parham Reisi; Maryam Radahmadi (Iranian Journal of Basic Medical Sciences, 2017)
Objective(s): Cholecystokinin (CCK) has been proposed as a mediator in stress. However, it is still not fully documented what are its effects. We aimed to evaluate the effects of systemic administration of CCK exactly before induction of stress on spatial memory and synaptic plasticity at CA1 in rats. Materials and Methods: Male Wistar rats were divided into 4 groups: the control, the control-CCK, the stress and the stress-CCK. Restraint stress was induced 6 hr per day, for 24 days. Cholecystokinin sulfated octapeptide (CCK-8S) was injected (1.6 µg/kg, IP) before each session of stress induction. Spatial memory was evaluated by Morris water maze test. Long term potentiation (LTP) in Schaffer collateral-CA1 synapses was assessed (by 100 Hz tetanization) in order to investigate synaptic plasticity. Results: Stress impaired spatial memory significantly (P